Young Mothers, (Pre-)Eclampsia and Other Factors Related to Preterm Birth in Two Hospitals in Jakarta - Bunga Anggraini, A (KnE Life Sciences, 2019)
Based on WHO data, the preterm birth rate in Indonesia in 2010 is 15.5 per 100 live births. Preterm birth is one of death leading cause in children under five years old because it can lead to severe complications. This study aimed to identify several factors related to preterm birth. The cross-sectional study was conducted in two selected hospitals in Jakarta from January 1st through December 31st, 2011. Data collected from medical records among women who delivered in those hospitals. The analysis performed by using multivariate logistic regression. This study collected 4191 samples. Eight hundred five examples were included in this analysis while remain samples excluded due to incomplete data records and post-term birth. The prevalence of preterm delivery in two hospitals was 14.84%. Compared to women in 20-34 years age group, a young mother with aged 17-20 years old had 3.37 fold higher chance to have preterm birth [adjusted odds ratio (ORa)=3.37; p=0.018]. Meanwhile, mothers with (pre-)eclampsia had 3.76 fold higher chance to have a preterm birth (ORa=3.76; p=0.0005). Furthermore, women with antepartum hemorrhage had a higher chance to have a preterm birth (ORa=12.52; p= 0.0005). A young mother, women who work in military/policy/civil servants/ state, (pre-)eclampsia mother, and mother with antepartum hemorrhage had a higher risk of preterm birth in selected hospitals in Jakarta. Keywords: a young mother, (pre-)eclampsia, antepartum hemorrhage, preterm birth